Recovery time variation during sprint interval training impacts amateur soccer players adaptations – a pilot study - Diker, Gürkan; Darendeli, Abdulkerim; Chamari, Karim; Dellal, Alexandre; Müniroğlu, Sürhat; Ön, Sadi; Özkamçı, Hüseyin (Biology of Sport, 2023)
The objective of the present study was to investigate the selected performance adaptations of amateur soccer players to 2 different running-based sprint interval training (SIT) protocols with different recovery intervals and work-rest ratios (1:5 & 1:1). Twenty-three subjects (age 21.4±1.1 years; height 175.4±4.7 cm; body mass 69±6.4 kg) participated in the study. Before the 6-weeks training period, participants completed 3-weeks of low-intensity training preparation. Subsequently, the pre-tests (anthropometric measurements, repeated sprint test [12×20-m with 30-s recovery intervals], Yo-YoIRT1 & Yo-YoIRT2 and treadmill VO2max test) were conducted. Thereafter, participants were randomly divided into 3 sub-groups (1 – SIT with 150 s recovery intervals [SIT150, n = 8]; 2 – SIT with 30 s recovery intervals [SIT30, n = 7]; and 3 – control group [CG, n = 8]). SIT150 and SIT30 training groups completed sprint interval training (2-days/week; 30-s all-out running, 6–10 repetition with 150 s recovery intervals for SIT150 and 30 s for SIT30 groups, respectively), a soccer match (1-day) and routine soccer training (3-days) per week. The CG attended only routine training sessions and the soccer-match (4-days). The study experiments and the trainings were conducted during off-season. Yo-YoIRT1, Yo-YoIRT2, and VO2max were significantly improved both in SIT30 and SIT150 (p < 0.05) groups. Yo-YoIRT1 and VO2max were also significantly improved in CG (p < 0.05). Both the SIT150 and SIT30 training were shown to improve Yo-YoIRT1, Yo-YoIRT2 and VO2max performance compared to the control group, nevertheless, SIT150 was more efficient in improving the Yo-YoIRT1, Yo-YoIRT2 than SIT30. The authors of this study suggest using SIT150 to induce more effective performance outputs in amateur soccer players.